Recent advances in dual response molecular probes for biothiols - Master Mwafulirwa; Khamis Abdalla; Wenhai Bian; Hongbei Wei; Liren Xu; Wanyi Yu; Zhang Hui; Qi Yang; Xiaolong Sun (Smart Molecules)
Abstract The detection of biothiols such as cysteine (Cys), homocysteine (Hcy), and glutathione (GSH) are critical for understanding their roles in biology and their involvement in various physiological and pathological processes. Recently, significant progress has been made in constructing fluorescent probes capable of detecting and visualizing biothiols. This review provides an in‐depth look at the latest advancements in simultaneous and selective molecular probes, focusing on developments over the last 5 years. We examine design techniques, sensing mechanisms, and imaging methods to assess their effectiveness and responsiveness to thiols. Additionally, we discuss the prevailing challenges and offer recommendations to address them.